PRINCIPLE APPROACH TO FORMING AND IMPLEMENTING AN EFFECTIVE SYSTEM OF ENTERPRISE'S ECONOMIC SECURITY UNDER CONDITIONS OF ECONOMIC RECOVERY (Development Service Industry Management, 2023)
The methodological and practical recommendations for the formation and implementation of an effective system of economic security at enterprises under conditions of the post-war recovery of the national economy are substantiated. The author's interpretation of the category «enterprise security» is proposed as a set of organizational, technical, managerial, and personnel measures that ensure the enterprise's stable functioning within the defined tasks of its development under the influence of destabilizing factors of the external environment. This made it possible to determine the content of the scientific categories «financial security of the enterprise» and «personnel security of the enterprise». At the conceptual level, the components of the mechanism for managing the financial security of the enterprise are substantiated, which, together with the process of its management, form the basis of the general system for managing the financial security of the business entity. It is recommended to consider the personnel security subsystem as an essential component in the structure of a modern enterprise's human resources management system, which combines it with the economic security system. A principled approach to understanding the role and place of the subsystem of financial and personnel security in the general system of the enterprise's economic security was formed, which made it possible to reveal in more detail the functional purpose of these subsystems and generalize the main elements (subjects and objects of management). The main areas of operation of the enterprise's economic security system under conditions of risks of economic activity and threats of the external environment are specified. The stages of evaluating the effectiveness of the enterprise's economic security system based on the resource and functional approach were considered. The practical implementation of the proposed author's approach will contribute to a proper mechanism for monitoring the enterprise's economic security system and a clear division of work between functional executors. The tasks of forming the enterprise's financial and personnel security subsystems are summarized.
Keywords: business security; enterprise security; economic security; the enterprise's economic security system; financial security; the enterprise's financial security management mechanism; personnel security; enterprise personnel security subsystem; the process of evaluating the economic security of the enterprise; digitalization of the national economy